1994
DOI: 10.1038/bjc.1994.200
|View full text |Cite
|
Sign up to set email alerts
|

Helix pomatia agglutinin binding in human tumour cell lines: correlation with pulmonary metastases in nude mice

Abstract: Summary The extent of lectin binding by three human melanoma (LOX, FEMX-I and SESX) and two sarcoma lines (MHMX and OHSX) was related to their potential for experimental metastasis formation in athymic nude mice. The Helix pomatia agglutinin (HPA), which recognises the N-acetyl-D-galactosamine ligand, showed differential binding to the cell lines in a manner that correlated with their ability to give lung colonies after i.v. injection in the mice (P<0.005). The degree of HPA binding and lung colony formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Also, intensely HPA-positive and metastatic cell line MeWo shows a tumour growth phase of 90 days, which has to be taken into consideration, concerning therapeutic studies. Kjonniksen et al (1994) demonstrated that the metastatic cell line LOX showed strong HPA binding, which is in parallel to our results. Additional results by that group showed, that the HPAnegative cell line FEMX-1 was not metastatic after iv injection, which is in contrast to our results, where all primary FEMX-1 tumours expressed HPA-binding sites and developed metastatic deposits in the lungs of 7/10 mice.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Also, intensely HPA-positive and metastatic cell line MeWo shows a tumour growth phase of 90 days, which has to be taken into consideration, concerning therapeutic studies. Kjonniksen et al (1994) demonstrated that the metastatic cell line LOX showed strong HPA binding, which is in parallel to our results. Additional results by that group showed, that the HPAnegative cell line FEMX-1 was not metastatic after iv injection, which is in contrast to our results, where all primary FEMX-1 tumours expressed HPA-binding sites and developed metastatic deposits in the lungs of 7/10 mice.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, subcutaneous injection of tumour cells, as presented here, warrants that the metastatic cascade as a whole can be analysed, whereas intravenous (iv) injection of tumour cells, as sometimes described by others, results in dissemination rather than in metastasis (Kjonniksen et al, 1994). For malignant melanoma, in particular, subcutaneous injection has the advantage of being an almost orthotopic model and therefore, reflects the clinical situation from the anatomical point of view more closely than the aforementioned iv injection.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…To examine the correlation in LOX cells between loss of Cosmc transcripts and Tn expression, we examined whether LOX cells were stained by HPA, as previously reported (23). LOX cells bound well to HPA and had poor binding to PNA.…”
Section: Lsc Cells Lacking T-synthase Activity Contain Mutatedmentioning
confidence: 99%
“…[13][14][15][16] The osteosarcoma cell line, OHS, was established from a bone tumor biopsy. 17 SK-MEL-28 (human melanoma), MeWo (human metastatic melanoma), A549 (human lung carcinoma), SK-BR-3 (human breast adenocarcinoma) and HeLa (human cervix epithelial adenocarcinoma) were obtained from the American Type Culture Collection (Rockville, MD).…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%